PENYIARAN ISLAM MELALUI MEDIA CETAK (KONSEP IDEAL, PROSPEK DAN TANTANGANNYA) - Ritonga, Elfi Yanti (Jurnal Ilmiah Al-Hadi, 2018)
Islam is a religion of da'wah which always encourages its followers to always actively carry out da'wah activities. As a religion of da'wah, Islam requires its people to internalize, transmit, diffuse, transform and actualize Islamic law by various methods and media. The use of print media in the implementation of Islamic da'wah is called Islamic broadcasting. Islamic Broadcasting is all activities which purpose to disseminate the teachings of Islam to the public in order to understand and practice it. One of the communication media that can be utilized for Islamic broadcasting is the print media. Islamic broadcasting through print media has special advantages when compared to da'wah in verbal communication and also other media. Therefore, Islamic broadcasting through print media must be handled professionally which based on journalistic code of ethics in accordance with Islamic teachings. Thus, Islamic broadcasting in print media will give maximum results.